Analysis of residual sludge stored in UASB of a WWT in Petrolina-PE-Brazil - Santos, Erick de Aquino; Xavier, Keyla Vitória Marques; Paiva, Marcella Vianna Cabral; Amorim, Miriam Cleide Cavalcante de; Diniz, Michely Correia (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Anaerobic digestion is a process that occurs through microorganisms in an anoxic condition and aims to digest organic matter resulting mainly in biogas. This process is common in wastewater treatment WWTs (Waste Water Treatment), which usually occur in bioreactors. In Brazil the most widespread is the UASB (Upflow Anaerobic Sludge Blanket) reactor due to its temperature conditions, which found in the country an ideal parameter. Archeas make up the microbiota responsible for digestion acting in the final stage of methanogenesis. The studies of these organisms are mainly through metagenomics, because laboratory cultivation is difficult. Therefore, the research aimed to study the physical and molecular parameters of the sludge. Four UASB reactors from WWT Center in Petrolina – Pernambuco- Brazil were evaluated. For the DNA extraction process the adapted protocol was applied, the physical analysis of the solids obeyed the determinations of APHA (2005). DNA extraction was achieved with the modified protocol and demonstrated a high concentration of DNA present in the samples, being the 4 most abundant reactor. Physical quantifications of the solids analysis showed that the values found are in compliance with current standards.